METODOLOGIA DE RESOLUÇÃO DE PROBLEMAS: ESINO E APRENDIZAGEM DE CONCEITOS DE MATEMÁTICA FINANCEIRA NO EJA - Miron, Tatiele Fátima (2013)
This dissertation has as its theme the teaching and learning of Mathematical Finance through the resolution of problems in the education of young people and adults (EJA). Its objective is to investigate the contributions of the use of the methodology of Problem Solving in the teaching-learning process in the construction of the concepts of financial mathematics with students of this modality of education. This research has had a character of conducting qualitative, and for this it was used as an instrument of data collection the participant observation recorded by means of a field diary where were reported all the events that took place in class, as well as documents produced in the resolutions of the problems, applied to twenty students of the second stage of the EJA of a private college, located in the town of Ijuí, in addition to the completion of tasks in computer lab on the subject. The problems were prepared from issues of daily life of students, involving the content of financial mathematics. It was possible to diagnose that students had problems of interpretation of listed the problems; relating to the withdrawal of the data and as relate them. Through this research it can be concluded that the application of the method of resolution of problems was valid, a time that allowed the students to the achievement of a collective work and collaborative, in addition to developing, ourselves, greater autonomy in the construction of their own knowledge. The researcher also provided the diagnosis of gaps in relation to learning through education based on direct application of formulas to the detriment of the contextualization of content.